Relação entre professoras negras e brancas no interior do sistema educacional em Lucas do Rio Verde-MT - Perotoni, Cleonice (2016)
The present survey, conducted in a public school in Lucas do Rio Verde – MT, aims to understand how the relationship are established between African-American teachers and the White teachers, and analyze the form of treatment given to African-American teachers arising from the management group. As a methodological procedure, the Exploratory Research was used, having as tools of data collection the semi-structured interviews, non-participant observation and document analysis – Pedagogical Policy Project from the school, City Plan for Education and Curricular Proposal from the city. The survey results show that the African- American teachers have difficulties to build their identity about their White peers, having to prove their intellectual ability to obtain professional recognition and social mobility in Education. The survey also reveals that the White teachers and the management team in the surveyed schools treat African-American teachers in a different/inferior way. This different treatment makes the African-American teachers face racial discrimination and perverse racism in both public schools in Lucas do Rio Verde. This fact was found as a fighting that makes the African-American teachers face discrimination and racial prejudice in the professional space of school.